Thermomechanical Analysis of Cement Hydration Effects in Multi-layered Pier Head Concrete: Finite Element Approach - Ahmad, Mohammad Ismail Ramadan; Irawati, Inggar Septhia; Awaludin, Ali; Siswosukarto, Suprapto (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
Mass concrete plays a crucial role in infrastructure development, yet its complex thermo-mechanical behavior poses challenges, especially in the construction of multi-layered structures like pier heads. This study investigated the thermo-mechanical behavior of a pier head during its concreting process in three stages, including the influence of temperature differences that impact the thermomechanical balance of the concrete. By utilizing the ABAQUS software, thermo-mechanical analysis was conducted to simulate temperature fluctuations during cement hydration. The model integrates thermal analysis to simulate temperature fluctuations during cement hydration and stress distribution during construction, validated through mesh convergence studies and field data comparison. The mechanical analysis considered concrete properties, temperature variations, and construction phase. Nonlinear material behavior and contact interactions between layers were incorporated to obtain a realistic simulation. The results indicated that a multi-layer system can balance temperatures, reducing thermal stress-induced cracking risks. Furthermore, specific test points within the pier head were assessed, revealing potential internal cracks by comparing thermal stresses to the concrete’s tensile strength. This research offers insight into pier head conditions during construction, highlighting critical stress zones, crack prediction, and construction sequence efficacy.